Rasionalitas Sosial-Ekonomi dalam Penyelesaian Pengangguran Terselubung Petani Sawah Tadah Hujan - Adriani, Dessy (UI Scholars Hub, 2015)
Disguised unemployment experienced by farmers in Indonesia are often caused by Zero Marginal Productivity of Labor . However, the completion of disguised unemployment has been only focused on the improvement of the economic structural transformation from agriculture to industry as an aspect of macro analysis, without considering aspects of micro analysis. Though micro analysis through socioeconomic rationality farm households can solve problems underemployment get to the root of the problem, because the basic analysis departs from the social and economic rational behavior. The research was conducted in the village of East Mount Merapi Flower District of Lahat. The research technique is a survey method. Sampling using the simple random method. Socioeconomic rationality analysis of disguised unemployment completion done with tabulation analysis, mathematics, and simulation. The analysis shows there has been a degree of disguised unemployment in farm households. Farmers through social rationally overcome disguised unemployment: (1) Differentiation of the structure of the work to other farming sectors and non- agricultural (new occupation), and (2) Reduction of non-family labor in farming activities to maximize the potential of household labor. This social rationals have economic impact on the reduction of disguised unemployment at 69 percent and 267 percent increase in revenue at the micro level. Thus, socioeconomic rationality farm households can solve problems disguised unemployment at the micro level.